Sequential therapy for 10 days versus triple therapy for 14 days in the eradication of Helicobacter pylori in the community and hospital populations: a randomised trial - Liou, Jyh-Ming (Gut, 2016)
OBJECTIVE: Significant heterogeneity was observed in previous trials that assessed the efficacies of sequential therapy for 10 days (S10) versus triple therapy for 14 days (T14) in the first-line treatment of Helicobacter pylori. We aimed to compare the efficacy of S10 and T14 and assess the factors affecting their efficacies. DESIGN: We conducted this open-label randomised multicentre trial in eight hospitals and one community in Taiwan. 1300 adult subjects with H pylori infection naïve to treatment were randomised (1:1) to receive S10 (lansoprazole and amoxicillin for the first 5 days, followed by lansoprazole, clarithromycin and metronidazole for another 5 days) or T14 (lansoprazole, amoxicillin and clarithromycin for 14 days). All drugs were given twice daily. Successful eradication was defined as negative (13)C-urea breath test at least 6 weeks after treatment. Our primary outcome was the eradication rate by intention-to-treat (ITT) and per-protocol (PP) analyses. Antibiotic resistance was determined by agar dilution test. RESULTS: The eradication rates of S10 and T14 were 87.2% (567/650, 95% CI 84.4% to 89.6%) and 85.7% (557/650, 95% CI 82.8% to 88.2%) in the ITT analysis, respectively, and were 91.6% (556/607, 95% CI 89.1% to 93.4%) and 91.0% (548/602, 95% CI 88.5% to 93.1%) in the PP analysis, respectively. There were no differences in compliance or adverse effects. The eradication rates in strains susceptible and resistant to clarithromycin were 90.7% and 62.2%, respectively, for S10, and were 91.5% and 44.4%, respectively, for T14. The efficacy of T14, but not S10, was affected by CYP2C19 polymorphism. CONCLUSIONS: S10 was not superior to T14 in areas with low clarithromycin resistance. TRIAL REGISTRATION NUMBER: NCT01607918.